2019
DOI: 10.7717/peerj.6343
|View full text |Cite
|
Sign up to set email alerts
|

The identification of gene signature and critical pathway associated with childhood-onset type 2 diabetes

Abstract: In general, type 2 diabetes (T2D) usually occurs in middle-aged and elderly people. However, the incidence of childhood-onset T2D has increased all across the globe. Therefore, it is very important to determine the molecular and genetic mechanisms of childhood-onset T2D. In this study, the dataset was downloaded from the GEO (Gene Expression Omnibus database); it includes 24 healthy children, 43 children with newly diagnosed Type 1 diabetes (T1D), and 12 children with newly diagnosed T2D. These data were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…However, a study revealed that the expression of NAMPT was of no difference between simple steatosis and NASH [ 25 ]. NAMPT also contributed to the regulation of insulin secretion in the pancreatic β-cells [ 22 ] and diabetes mellitus [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study revealed that the expression of NAMPT was of no difference between simple steatosis and NASH [ 25 ]. NAMPT also contributed to the regulation of insulin secretion in the pancreatic β-cells [ 22 ] and diabetes mellitus [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the molecular level dysfunction of islet cells of type 2 diabetes can provide effective treatment and more predictive and diagnostic biomarkers. For example, Jia et al [12] identified marker genes for childhood-onset type 2 diabetes from one GEO dataset by performing DEGs, weighted co-expression network analysis (WGCNA), GO and KEGG enrichment, PPI network, diseases and transcription factors (TFs) related to critical genes analysis. Shao et al [13] identified that the glucocorticoid was central in the pathogenesis of type 2 diabetes from three GEO datasets by integrated method including DEGs screen, gene functional enrichment, PPI network analyses, drug–gene interactions and genetic association of DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the DEG to evaluate the different 5-hmC levels of cfDNA in plasma between healthy individuals and CRC patients by the limma package [ 14 ]. The parameter settings were set according to a previous study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…We used the WGCNA package [ 16 ] to determine the coexpression modules and the interconnectedness between each module, and the coexpressed genes in the control and CRC patients according to a previously published method [ 15 ].…”
Section: Methodsmentioning
confidence: 99%